Fraudulent Financial Reporting Analysis Using Fraud Diamond Theory in Indonesia Manufacturing Industry - Rinaningsih; Chandra, Casey; Khalila, Shabrina Zahra; Sinaga, Rifeald Romauli (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2023)
This study investigates the impact of the fraud diamond theory on financial statement fraud in companies, considering pressure, opportunity, rationalization, and capability as its components. The aim of this study is to make a contribution by assisting in identifying and preventing occurrences of fraudulent financial reporting. It analyzes 785 observations from 157 manufacturing companies listed on the Indonesia Stock Exchange between 2017 and 2021, using secondary data from annual reports and capital IQ. The research categorizes data into indicated and non-indicated fraudulent financial reporting, identified through p-score and z-score comparisons. Logistic regression using STATA is the chosen research method. The findings reveal that external pressure and financial targets, among the pressure elements, significantly contribute to a negative impact on fraudulent financial reporting. On the other hand, rationalization, measured by auditor changes, exhibits a significant positive influence. However, financial instability, opportunity assessed through effective monitoring and audit committee presence, and capability measured by director changes do not significantly affect the occurrence of fraudulent financial reporting. Therefore, this study is expected to contribute by helping identify and prevent fraudulent financial reporting.